RISK FACTORS ASSOCIATED WITH MORTALITY FROM OMICRON VARIANT OF SARS-CoV-2 IN REPUBLIC OF NORTH MACEDONIA - Kochinski, Dragan; Velikj Stefanovska, Vesna; Popovska Kljuseva, Svetlana; Pollozhani, Enkela; Memeti, Shaban (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
In 2019, Wuhan registered an epidemic of a severe form of pneumonia. On January 7, 2020, the pathogen was identified as SARS-CoV-2. COVID-19 causes acute and fatal disease with an average mortality rate of 2%. Based on evidences, risk factors include older age, male gender, and ethnicity, as well as presence of comorbidities. Five variants of concern have been identified by WHO. The original variant of Omicron was first reported in Botswana and South Africa in November 2021. The research aimed to analyze the risk factors associated with mortality from Omicron variant of SARS-CoV-2 in the Republic of North Macedonia. The research was a prospective cross-sectional study that elaborated the mortality from Omicron variant of SARS-CoV-2 in the Republic of North Macedonia during the period December 2021/2022. The analysis included demographic characteristics, symptomatology, comorbidities, and vaccination status. The analysis showed that the male gender (OR=1.83; 95%CI=1.66-2.02), the age â‰¥60 (OR=33.98; 95%CI=28.53-40.47), the positive comorbidity status (OR=37.26; 95%CI=30.62-35.54), and hospitalization (OR=362.7; 95%CI=309.7-424.8) significantly positively associated with death from Omicron variant. Complete vaccination and/or booster dose significantly negatively associated with hospitalization and mortality of Omicron variant reducing the probability for hospitalization (46%) and death (56%) respectively. Male patients, older age group and comorbidities positively associated with death from the Omicron variant of SARS-CoV-2. The results of this study can be used to prepare the national health system for similar future epidemic crises. Keywords: Omicron SARS-CoV-2, mortality, hospitalization, vaccination